A Historical Analysis of Remittances from Diaspora and Development in Nigeria, 1960-2018 - Oladele Adeoti, Ezekiel (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Nigerian Diasporas constitute a formidable group of people who have been playing considerable role in the unending search for solutions to the socio-economic and political problems affecting the progress of Nigeria. This paper, critically examined the contributions of the Nigerian Diasporas to the growth and development of Nigeria between 1960 and 2018. The data for the study was derived from secondary sources, including official documents, reports, newspaper and journal articles on Nigerian and African Diasporas. The paper argued that the Diasporas contributions came in two major forms: Diasporas remittances and human capital, through which they transferred their economic, political, social, intellectual ideas, skills and knowledge for the overall benefit of Nigerians. The paper added that in spite of the several militating factors, the Nigerian Diasporas have proved themselves as veritable purveyors of national development. The paper concluded that despite the huge sums of money remitted into the Nigerian economy annually, poverty, diseases and underdevelopment are still prevalent. The paper recommended good governance, probity, transparency and accountability on the part of Nigerian government to encourage more Nigerians living abroad to relocate to Nigeria and contribute their much needed quotas to national development in Nigeria.